(untitled) (Advancements in Homeopathic Research, 2023)
Background & Objectives It is a degenerative disorder affecting the cervical spine, where degeneration of the intervertebral disc leads to changes in surrounding bones and ligaments, gradually there is a formation of a bar-like structure protruding at intervertebral areas. The fifth and sixth cervical vertebrae are most commonly involved. My study is to understand the effectiveness of the Miasmatic approach of Homoeopathy in treating cervical spondylosis and also to assess the severity of neck pain which affects a patient’s daily life by using the Neck Disability Index Scale. Methods This Prospective experimental study which is conducted at Vinayaka Missions Homoeopathic Medical College and Hospital, Salem, during the year 2015-2017. 30 patients were selected based on Purposive sampling based on inclusion and exclusion criteria. Neck Disability Index Score was taken as an assessment scale in which all symptoms of the patients were collected before and after the treatment. After case taking the symptoms were analysed, and evaluated and the totality of symptoms worked out based on Dr J T Kent’s Repertorization method with consideration of Miasm present in each case. Miasmatic analysis was done based on mental and physical generals, Past history, presenting complaint and family history of the patient. Paired t-test was used to assess the improvement after the treatment based on the score of the Neck disability index. X-ray was taken before and after the treatment. Cervical Radiculopathy and Myelopathy were diagnosed by different clinical examinations. This study protocol was approved by the Institutional Ethical Committee of VMHMC & Hospital, Salem. Consent was obtained from the patient and all the patients were followed for 6-12 months.